Neurogenic Shock in ICU - Ahmed, Ahsan; Bose, Payel (Journal of Nepalese Society of Critical Care Medicine, 2024)
Neurogenic shock is a state characterized by hypotension, bradycardia, and dysautonomia. It is an important condition associated with lesions in various regions along the neuraxis. The most common cause is acute spinal cord injury (SCI). Because the typical autonomic reflexes may be either abolished or dysregulated, appropriate treatment requires an understanding of the neuroanatomic substrate for the change. The time frame for manifestation of neurogenic shock is variable and can quickly progress to cause secondary injury or death, so appropriate monitoring requires a high level of suspicion and diligence. Many pharmacological interventions are tried but their efficacy is still questionable and need more prospective studies to accurately assess their real value. The best timing for neurosurgical intervention is also debatable. The initial management in the emergency room is fundamental for improved outcome with respect to neuroplasticity and neuronal rehabilitation.